1969
DOI: 10.1107/s0567740869003086
|View full text |Cite
|
Sign up to set email alerts
|

Phase determination for the estriol structure

Abstract: Some recently secured results make possible the implementation of a program for direct phase determination first proposed over ten years ago. Application is made to the evaluation of the phases for the estriol structure. The values of 1805 structure invariants, cos (tp~ + ~2+~p3), lead, by means of a novel least-squares technique, to the determination of 103 phases. Employing the tangent formula, these 103 phases are used to obtain the values of the 1023 phases whose corresponding normalized structure factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

1970
1970
1993
1993

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 1 publication
0
33
0
Order By: Relevance
“…Secondly, numerical tests indicated that (1) tended to produce unreliable cosine estimates as a consequence of the unavoidable overlap of vectors in the Patterson function and attempts were made to modify these calculations to improve the results. One variant of (1) that was developed to mitigate the Patterson-function overlap problem, subsequently referred to as the TPROD formulation (Hauptman, Fisher, Hancock & Norton, 1969), was [EhE_kEk_hl COS (~h--~k+ (~k-h) ~' --R3 + K~, (2) R3 = ¼ +lEhl 2 +lEkl 2 + I Ek-f --{], = < (I Ed ~/2 -~)(I E,-kl 1/2 _ ~)(i El-hi 1/2 _ ~)),, where ~= (Ehl~/2)h and K is a scale factor that can be adjusted as a function of the magnitude of ]EhEkEk-hl in an effort to fit the calculated distribution of cosines to the theoretical distribution. The MDKS formula (Fisher, Hancock & Hauptman, 1970) is an alternate variant of (1) that utilizes conditional averages,…”
Section: ~-N-'/2(iehl 2 + Iekl 2 + [Ek_h] 2-2)mentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, numerical tests indicated that (1) tended to produce unreliable cosine estimates as a consequence of the unavoidable overlap of vectors in the Patterson function and attempts were made to modify these calculations to improve the results. One variant of (1) that was developed to mitigate the Patterson-function overlap problem, subsequently referred to as the TPROD formulation (Hauptman, Fisher, Hancock & Norton, 1969), was [EhE_kEk_hl COS (~h--~k+ (~k-h) ~' --R3 + K~, (2) R3 = ¼ +lEhl 2 +lEkl 2 + I Ek-f --{], = < (I Ed ~/2 -~)(I E,-kl 1/2 _ ~)(i El-hi 1/2 _ ~)),, where ~= (Ehl~/2)h and K is a scale factor that can be adjusted as a function of the magnitude of ]EhEkEk-hl in an effort to fit the calculated distribution of cosines to the theoretical distribution. The MDKS formula (Fisher, Hancock & Hauptman, 1970) is an alternate variant of (1) that utilizes conditional averages,…”
Section: ~-N-'/2(iehl 2 + Iekl 2 + [Ek_h] 2-2)mentioning
confidence: 99%
“…Tangentformula methods for small-molecule determinations have traditionally relied on the 0 (modulo 27r) probability estimate for these 'triples' (Karle & Hauptman, 1956). Efforts to extend these techniques to larger structures have required more precise estimates to be obtained for these phase invariants, though use of algebraic formulae (Karle & Hauptman, 1957;Vaughan, 1958;Hauptman, 1964;Hauptman, Fisher, Hancock & Norton, 1969;Karle, 1970;Duax, Weeks & Hauptman, 1972;, determinantal joint probability distributions (Tsoucaris, 1970;Messager & Tsoucaris, 1972;Giacovazzo, 1976Giacovazzo, , 1977aKarle, 1979Karle, , 1980 or probabilistic formulae, as applied to isomorphous-replacement or anomalous-dispersion data (Hauptman, 1982;Giacovazzo, 1983;Fortier, Moore & Frazer, 1985) and to the extended neighborhoods or phasing shells of data that define higher-order relationships into which these triples have been suitably embedded (Hauptman, 1975;Giacovazzo, 1977b;Karle, 1982). This report describes a new method to estimate three-phase 0108-7673/93/030545-13 $06.00 invariants based on examination of the frequency distribution of ILl magnitudes that complete a family of conditionally constructed quadrupoles that are common to the evaluated triple.…”
Section: Introductionmentioning
confidence: 99%
“…We can see that this imitative function is practically identical with the function minimized by the program YZARC (Baggio, Woolfson & Germain, 1978;Wright, 1983). Hauptman, Fisher, Hancock & Norton (1969) …”
Section: Appendix 2 Examples Of Imitative Functionsmentioning
confidence: 99%
“…A lot of research has been undertaken to modify the B3.o formula (e.g. Hauptman, 1964;Hauptman, Fisher, Hancock & Norton, 1969;Karle, 1970;Fisher, Hancock & Hauptman, 1970). All these approaches tried to calculate the exact value of the 0108-7673/89/070468-04503.00 cosine invariant rather than giving a statistical interpretation of it.…”
Section: Introductionmentioning
confidence: 99%